2017
DOI: 10.17508/cjfst.2017.9.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical, microbial and sensory properties of kunu zaki beverage sweetened with black velvet tamarind (Dialium guineense)

Abstract: Indexing p. 1  Editorial Bord p. 1  Guide for Authors p. 3  Manuscript preparation p. 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
2
7
1
Order By: Relevance
“…The β‐carotenoid has antioxidant properties that can help neutralize free radicals—reactive oxygen molecules potentially damaging lipid in cell membranes, proteins, and DNA. In this study, we reported lower values than values reported for Lannea kerstingii (Ouilly et al., ), Dialium guineense (Abiodun et al., ), and tropical leafy vegetables (Djuikwo, Ejoh, Gouado, Mbofung, & Tanumihardjo, ). De Caluwe, Halamova, and Van Damme () reported low carotenoids in T. indica fruit pulp.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…The β‐carotenoid has antioxidant properties that can help neutralize free radicals—reactive oxygen molecules potentially damaging lipid in cell membranes, proteins, and DNA. In this study, we reported lower values than values reported for Lannea kerstingii (Ouilly et al., ), Dialium guineense (Abiodun et al., ), and tropical leafy vegetables (Djuikwo, Ejoh, Gouado, Mbofung, & Tanumihardjo, ). De Caluwe, Halamova, and Van Damme () reported low carotenoids in T. indica fruit pulp.…”
Section: Discussioncontrasting
confidence: 64%
“…The values recorded in this study were higher than those reported by Sadiq, Duruminiya, Balogun, Kwada, and Izuagie (2016); Sulieman et al (2015);Chiteva and Kituyi (2006) andEl-Siddig et al (2006). Vitamin C contents of other documented plant species were within the range reported for Dialium guineense(Abiodun et al, 2017) but lower than values reported for olive fruit(Muhammad et al, 2014).High vitamin C contents recorded in the samples especially pulp probably show the freshness of the samples, which corroborates the report of SLH (2017) that indicated high contents in fresh fruits and vegetables. According toDimari and Hati (2010), a number of researchers have attributed factors such as fruit type and storage methods, temperature, microorganism, and package type on the stability of vitamin C Hiremath et al (2016).…”
supporting
confidence: 83%
See 2 more Smart Citations
“…This beverage became more widely accepted all over the country, owing to its refreshing qualities and nutritional benefits mostly derived from the source cereal grain and processing method 4 …”
Section: Introductionmentioning
confidence: 99%